2016
DOI: 10.1021/acsomega.6b00058
|View full text |Cite
|
Sign up to set email alerts
|

Library of Cationic Organic Dyes for Visible-Light-Driven Photoredox Transformations

Abstract: Organic dyes can be excellent catalysts for photoredox chemistry, offering low price, low toxicity, and an exceptional range of available materials. Their use has been limited because in comparison to their transition-metal catalysts the spectroscopic, kinetic, and electrochemical information available is far more limited. To remediate this situation, we have determined the necessary data for 14 readily available dyes with excellent potential as photoredox catalysts. We have also demonstrated the utility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 40 publications
0
80
0
2
Order By: Relevance
“…In this respect, the use of methylene blue (MB) as ap hotocatalyst [4a, 19] is advantageous since its low-energy absorption peak (l max = 654 nm), coupled with the down-conversion capabilities of the LSC-PM, results in avery effective use of the UV/Vis spectrum ( Figure 1b). [20] In particular,w ee nvisioned ac ombination between MB as photocatalyst and the fluorescent dye Lumogen Fr ed 305 (LR305) as the LSC luminophore. [21] LR305 is ap erylene bisimide-based dye widely used in LSCs due to its broad absorption spectrum, excellent photoluminescent quantum yield, and high photostability.…”
mentioning
confidence: 99%
“…In this respect, the use of methylene blue (MB) as ap hotocatalyst [4a, 19] is advantageous since its low-energy absorption peak (l max = 654 nm), coupled with the down-conversion capabilities of the LSC-PM, results in avery effective use of the UV/Vis spectrum ( Figure 1b). [20] In particular,w ee nvisioned ac ombination between MB as photocatalyst and the fluorescent dye Lumogen Fr ed 305 (LR305) as the LSC luminophore. [21] LR305 is ap erylene bisimide-based dye widely used in LSCs due to its broad absorption spectrum, excellent photoluminescent quantum yield, and high photostability.…”
mentioning
confidence: 99%
“…In addition, they investigated visible-light-promoted reductive dehalogenation with differentd yes, which included five sulfur-containing MB-related catalysts ( Table 3). [17] Up to 66 to 94 %o fmeso-1,2-dibromo-1,2-diphenylethane 35 can be converted within 5min to generate trans-stilbene 36.E xperiments performed with aU Vs ource in the presence of TMEDA 24 but 3 ]Cl 2 37 with trans-stilbene is two orderso fm agnitude higher than the SET quenching constant with TMEDA 24, which resulted in isomerization of the double bond (Scheme 5). Beyond the reactions above,aselectivef unctionalization of furan catalyzed by MB has also been reported, although with a relativelyh igher-energy visible-light source.…”
Section: Thiazine Dyesmentioning
confidence: 99%
“…In 2016, Scaiano et al. demonstrated a visible‐light‐promoted aza‐Henry reaction catalyzed by thiazine dyes (Table ) . Control experiments showed that oxygen was essential.…”
Section: Sulfur‐containing Photosensitizersmentioning
confidence: 99%
See 2 more Smart Citations